National Cultural Distance and Cross-Border Acquisition Performance - Morosini, Piero; Shane, Scott; Singh, Harbir (Journal of International Business Studies, 1998)
Previous theoretical research has argued that national cultural distance hinders cross-border acquisition performance by increasing the costs of integration. This article tests the alternative hypothesis that national cultural distance enhances cross-border acquisition performance by providing access to the target's and/or the acquirer's diverse set of routines and repertoires embedded in national culture. Using a multi-dimensional measure of national cultural distance and controlling for other effects, we examine a sample of 52 cross-border acquisitions that took place between 1987 and 1992, and find a positive association between national cultural distance and cross-border acquisition performance.